USING LINUX AS A ROUTER IN A COMPUTER NETWORK AT PT GRAHA SIDANG PRATAMA - Dony Priyadi; Sunarto Usna, Drs, MMSI (Jurnal Sistem Informasi, 2003)
This writing contains about networking system available at PT Graha Sidang Pratama especially in the use of an IP Address. The author explains how to work as well as the elements that influenced on the existing network system. in view of the problems experienced in these systems, the authors propose a new system to resolve the issue. This new system is used to optimize network usage and simplify network administrators to monitor network